POSTĘPOWANIE W SPRAWIE USTALENIA LOKALIZACJI INWESTYCJI CELU PUBLICZNEGO - WYBRANE ZAGADNIENIA - Grossmann, Tomasz (Wydział Prawa i Administracji UAM, 2005)
The act on spatial planning and spatial development of 27 March 2003 introduced two types of decisions relating to the conditions of site development: one, concerning public investment projects and one concerning the conditions of development of all other investments. While stressing in his paper the dualism of administrative procedure that arises from the above, the author focuses of the analysis of selected issues related to the instigation, the course, and possible ways of finalising the proceedings that determine the location of a public investment. Those proceedings show many discrepancies in relation to the general administrative procedure, and the regulation of those may lead to disputes as to how to interpret and apply them. The issues related to the legislative novum, being the possibility of issuing a decision concerning a public investment location by a voivode (region governor) have been given special attention. 55
DETERMINATION OF A LOCATION FOR A PUBLIC INVESTMENT - SELECTED ISSUES